Battery
By using high-concentration nonaqueous electrolyte and cross-linked modified (meth)acrylic acid termination glue layer in the battery, the safety hazards of the battery in the high-temperature environment are solved, and the battery high-temperature performance is improved and the battery cell stability is achieved. sex.
Patent Information
- Application Number
- CN202411287270.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-23
- Publication Date
- 2024-12-17
AI Technical Summary
Existing batteries are prone to safety accidents in high temperature environments, such as battery cells deforming, ignition or explosion. The main reason is that the electrode sheet termination tape loses adhesion under high temperature and high pressure and the electrolyte decomposes under high temperature and high voltage, resulting in deterioration of battery cells. .
Using high concentration of nonaqueous electrolyte and cross-linked modified (meth)acrylic acid termination adhesive layer, the synergistic effect of the positive electrode sheet and the nonaqueous electrolyte are formed to form a specific three-dimensional network structure, which enhances the adhesive force of the tape and Flexibility resistance, prevents the glue layer from aging and deforming the battery cell.
It significantly improves the high-temperature performance of the battery, delays the aging of the positive electrode sheet termination tape, avoids the problem of battery cell deformation and circulating lithium extraction, and improves the safety and life of the battery.
Smart Images

Figure CN119153755A_ABST
Abstract
Description
[0001] This disclosure is a divisional application of an invention patent application filed in China with application number 202111394925.5, application date November 23, 2021, and invention name “A Battery”. Technical Field
[0002] The present invention belongs to the technical field of batteries, and in particular relates to a high-voltage battery with excellent high-temperature performance. Background Art
[0003] In recent years, batteries have been widely used in smart phones, tablets, smart wearables, power tools, electric vehicles, etc. With the widespread use of batteries, consumers' requirements for battery energy density and usage environment are constantly increasing, which requires batteries to have excellent high-temperature safety performance at high voltage.
[0004] At present, there are safety hazards in the use of batteries. For example, when the battery is in some extreme use conditions such as continuous high temperature, serious safety accidents are prone to occur, and the battery cell is deformed, caught fire or even exploded. The main reason for these problems is that the adhesive layer of the battery pole termination tape is easily dissolved in the electrolyte under high temperature and high pressure and loses its adhesiveness, making the tape unable to play an effective fixing role, resulting in local deformation and warping of the battery cell or short circuit causing safety accidents; on the other hand, the electrolyte is easy to decompose under high temperature and high voltage, and redox decomposition occurs on the surface of the positive and negative electrodes to destroy the SEI film, causing the battery cell impedance to continue to increase and deteriorate the battery cell performance. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of the positive electrode termination tape warping and deformation when the existing battery is used in a high temperature environment, resulting in high temperature storage thickness failure of the battery cell and high temperature cycle lithium precipitation, the adhesive layer in the positive electrode termination tape being easily soluble in the non-aqueous electrolyte, and the non-aqueous electrolyte being easily oxidized and reduced and decomposed at the positive and negative electrode interfaces, and to provide a battery which is a high voltage battery and has excellent high temperature performance.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A battery, comprising a positive electrode sheet, a negative electrode sheet, a non-aqueous electrolyte and a separator; a positive electrode sheet termination tape is arranged at the paste tail of the positive electrode sheet; the non-aqueous electrolyte comprises a non-aqueous organic solvent and a lithium salt;
[0008] The area of the positive electrode termination tape is A cm 2 , the concentration of the lithium salt is B mol / L, the width of the positive electrode sheet is C cm, wherein the ratio of A to B is in the range of 2 to 20; the ratio of A to C is in the range of 1 to 3;
[0009] The positive electrode termination tape comprises a PET substrate and a (meth) acrylic acid termination adhesive layer coated on the surface of the PET substrate.
[0010] In the present invention, the (meth)acrylic acid refers to acrylic acid and / or methacrylic acid.
[0011] In the battery, the number of positive electrode sheet termination tapes is two, that is, one positive electrode sheet termination tape is disposed on both sides of the positive electrode current collector in the positive electrode sheet, and the area A of the positive electrode sheet termination tape refers to the area of the positive electrode sheet termination tape disposed on one side of the positive electrode current collector in the positive electrode sheet. Furthermore, the areas of the positive electrode sheet termination tapes disposed on both sides of the positive electrode current collector in the positive electrode sheet are the same.
[0012] According to the present invention, the ratio of A to B is 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any point value in the range formed by the two end points mentioned above. When the ratio of A to B is between 2 and 20, the high concentration of lithium salt in the non-aqueous electrolyte and the positive electrode termination tape can have a better synergistic effect; specifically, the high concentration of solute lithium salt is more conducive to enhancing the interaction between the solute and the solvent in the solution, and the free solvent molecules disappear to form a new non-aqueous electrolyte, that is, a high concentration non-aqueous electrolyte. At the current ratio, it is more conducive to the formation of a specific three-dimensional network structure of the non-aqueous electrolyte, and ions (such as lithium ions) form coordination with limited free solvent molecules and anions, which is significantly different from the free solvent molecules as the main body. Conventional low-concentration electrolyte can better slow down the aging of the (meth)acrylic acid termination tape after the positive electrode termination tape is immersed in the non-aqueous electrolyte, so that it still maintains good resistance to multiple flexures and adhesion, ensures that it still maintains constant tensile strength when immersed in the non-aqueous electrolyte, delays the aging failure of the positive electrode termination tape, and avoids the (meth)acrylic acid termination tape overflowing from the positive electrode termination tape and covering the surface of the positive electrode active material to cause pore blockage, improves the deformation of the battery cell caused by the warping of the positive electrode termination tape, and at the same time improves the edge lithium plating caused by pore blockage during the battery cell cycle.
[0013] According to the present invention, the ratio of A to C is 1, 1.2, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.5, 3 or any point value within the range formed by the two end points. When the ratio of A to C is between 1 and 3, the glue layer area of the positive electrode termination tape more reasonably covers the surface of the paste and the blank foil to reduce the influence of the electrolyte on the glue layer.
[0014] According to the present invention, a positive electrode termination tape is arranged at the paste tail of the positive electrode sheet, and the arrangement of the positive electrode termination tape can also fix the tail of the battery cell and cover the burrs of the cut edge of the positive electrode sheet to prevent the battery from short circuit and play a role of insulation protection.
[0015] According to the present invention, the area A of the positive electrode termination tape is 3 cm 2 ~120cm 2 Range; Exemplarily, the area A of the positive electrode termination tape is 3cm 2 , 5cm 2 、10cm 2 , 20cm 2 、30cm 2 、40cm 2 , 50cm 2 、60cm 2 、70cm 2 、80cm 2 、90cm 2 、100cm 2 、120cm 2 Or any point value within the range formed by the two endpoints mentioned above.
[0016] According to the present invention, the width C of the positive electrode sheet is between 1 cm and 120 cm; illustratively, the width C of the positive electrode sheet is 1 cm, 3 cm, 5 cm, 6 cm, 8 cm, 10 cm, 16 cm, 20 cm, 30 cm, 40 cm, 50 cm, 60 cm, 70 cm, 80 cm, 90 cm, 100 cm, 110 cm, 120 cm or any point value within the range formed by two end points.
[0017] According to the present invention, the thickness of the positive electrode termination tape is 8 μm to 20 μm.
[0018] According to the present invention, the (meth)acrylic acid termination glue layer comprises cross-linked modified (meth)acrylic acid and / or cross-linked modified (meth)acrylate.
[0019] According to the present invention, the crosslinking agent of the crosslinked modified (meth)acrylic acid and / or crosslinked modified (meth)acrylic acid ester comprises vinylene carbonate.
[0020] According to the present invention, the (meth)acrylate is selected from (meth)acrylate C 1-10 The alkyl ester is illustratively selected from at least one of isooctyl acrylate, n-butyl acrylate, methyl acrylate, ethyl acrylate, n-propyl acrylate and the like.
[0021] According to the present invention, the content of the vinylene carbonate accounts for 0.5 to 5 wt.% of the mass of the cross-linked modified (meth) acrylic acid and / or the cross-linked modified (meth) acrylate, for example, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 1.2 wt%, 1.5 wt%, 1.8 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 3.8 wt%, 4 wt%, 4.5 wt% or 5 wt%.
[0022] According to the present invention, the (meth)acrylic acid termination adhesive layer further comprises an auxiliary agent, and the auxiliary agent is, for example, at least one selected from antioxidants, inorganic fillers, and the like.
[0023] According to the present invention, the antioxidant is a commonly used antioxidant suitable for cross-linked modified (meth)acrylic acid and / or cross-linked modified (meth)acrylate.
[0024] According to the present invention, the inorganic filler is a conventionally used inorganic filler suitable for cross-linked modified (meth)acrylic acid and / or cross-linked modified (meth)acrylate.
[0025] According to the present invention, the concentration of the lithium salt is the molar percentage of the lithium salt in the non-aqueous electrolyte (in mol / L).
[0026] According to the present invention, the concentration B of the lithium salt is 1 mol / L to 6 mol / L; preferably, the concentration B of the lithium salt is 1.5 mol / L to 3 mol / L; for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 5 mol / L or 6 mol / L.
[0027] According to the present invention, the electrolyte additive also includes at least one of 1,3-propane sultone, 1,3-propylene sultone, fluoroethylene carbonate, vinyl sulfite, vinyl sulfate, lithium dioxalatoborate, lithium difluorophosphate, lithium difluorooxalatophosphate and vinyl vinyl carbonate, and its content accounts for 0 to 10 wt% of the total mass of the non-aqueous electrolyte.
[0028] According to the present invention, the non-aqueous organic solvent is selected from at least one of carbonates, carboxylates and fluoroethers, wherein the carbonate is selected from one or more combinations of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and methyl propyl carbonate; the carboxylates are selected from one or more combinations of ethyl propionate and propyl propionate; and the fluoroether is selected from 1,1,2,3-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0029] According to the present invention, the lithium salt is selected from at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.
[0030] According to the present invention, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer coated on one or both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder.
[0031] The positive electrode active material is selected from lithium cobalt oxide or lithium cobalt oxide doped with or coated with two or more elements selected from Al, Mg, Mn, Cr, Ti, and Zr. The chemical formula of the lithium cobalt oxide doped with or coated with two or more elements selected from Al, Mg, Mn, Cr, Ti, and Zr is Li x Co 1-y1-y2-y3-y4 A y1 B y2 C y3 D y4 O 2 ; 0.95≤x≤1.05, 0.01≤y1≤0.1, 0.01≤y2≤0.1, 0≤y3≤0.1, 0≤y4≤0.1, A, B, C, D are selected from two or more elements of Al, Mg, Mn, Cr, Ti, and Zr.
[0032] According to the present invention, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer coated on one side or both sides of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, a conductive agent and a binder.
[0033] The negative electrode active material is selected from graphite or a graphite composite material containing 1-12wt% SiOx / C or Si / C.
[0034] According to the present invention, the charging cut-off voltage of the battery is 4.45V or above.
[0035] According to the present invention, the battery is a lithium-ion battery.
[0036] In the present invention, the term "in the range of..." includes endpoint values. For example, "in the range of 2 to 20" means greater than or equal to 2 and less than or equal to 20.
[0037] The beneficial effects of the present invention are:
[0038] The present invention provides a battery, which is a high-voltage battery and has excellent high-temperature performance. The inventor of the present invention has found through intensive research that the high-temperature performance of the prepared battery cell can be effectively improved through the synergistic effect of the positive electrode termination tape and the non-aqueous electrolyte, and at the same time, the problem of lithium deposition at the edge of the electrode after the battery cell cycle can be solved, and the problem of the positive electrode termination tape warping and deformation when the battery is used in a high-temperature environment, resulting in failure of the high-temperature storage thickness of the battery cell and lithium deposition during high-temperature cycles, the adhesive layer in the positive electrode termination tape being easily soluble in the non-aqueous electrolyte, and the non-aqueous electrolyte being easily oxidized and reduced at the interface of the positive and negative electrodes can be avoided.
[0039] Specifically, a high concentration of solute lithium salt is more conducive to enhancing the interaction between the solute and the solvent in the solution, and the free solvent molecules disappear to form a new non-aqueous electrolyte, namely a high-concentration non-aqueous electrolyte. At the current ratio, it is more conducive to the formation of a specific three-dimensional network structure of the non-aqueous electrolyte. Ions (such as lithium ions) form coordination with limited free solvent molecules and anions, which is significantly different from the conventional low-concentration electrolyte with free solvent molecules as the main body. It can inhibit the electrolyte from soaking the tape, so that the (meth) acrylic acid termination adhesive layer maintains a better viscosity and is more stable and reduced. Liquefaction and fluidity can better slow down the aging of the (meth)acrylic acid termination tape after the positive electrode termination tape is immersed in the non-aqueous electrolyte, so that it still maintains good resistance to multiple flexures and adhesion, ensures that it still maintains constant tensile strength when immersed in the non-aqueous electrolyte, delays the aging failure of the positive electrode termination tape, and avoids the (meth)acrylic acid termination tape overflowing from the positive electrode termination tape and covering the surface of the positive electrode active material to cause pore blockage, improves the deformation of the battery cell caused by the warping of the positive electrode termination tape, and at the same time improves the edge lithium plating caused by pore blockage during the battery cell cycle.
[0040] Furthermore, as the lithium salt concentration increases, the operating voltage range of the non-aqueous electrolyte becomes wider, matching the high-voltage positive electrode material to achieve stable charging and discharging. The fewer flammable solvent molecules can alleviate the reaction between the electrolyte and the active oxygen generated by the positive electrode, thereby improving the battery life and safety.
[0041] Furthermore, the additives in the non-aqueous electrolyte can also form a strong electrode / electrolyte interface film on the surface of the positive and negative electrodes, optimize the embedding / ejection of ions (such as lithium ions) on the surface of the positive and negative electrodes, and improve the cycle performance of the battery.
[0042] Furthermore, the (meth) acrylic acid termination adhesive layer in the positive electrode termination tape contains vinylene carbonate, which can participate in the cross-linking polymerization of acrylic acid, so that the acrylic acid termination adhesive layer contains ethyl carbonate structural branches, making it more resistant to high temperature and high pressure, stabilizing the adhesive layer structure, and further improving the high temperature performance of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1This is a schematic structural diagram of a positive electrode sheet according to a preferred embodiment of the present invention.
[0044] Figure 2 This is a schematic structural diagram of a positive electrode sheet according to another preferred embodiment of the present invention.
[0045] Figure 3 for Figure 2 A side view of the positive electrode sheet.
[0046] Figure markings: 1—head of positive electrode sheet; 2—tail of positive electrode sheet; 3—empty foil area; 4—termination tape of positive electrode sheet; 5—tail of positive electrode sheet on one side; 6—termination tape of positive electrode sheet on one side; 7—tail of positive electrode sheet on the other side; 8—termination tape of positive electrode sheet on the other side. DETAILED DESCRIPTION
[0047] In the present invention, the "positive electrode sheet termination tape" refers to a tape arranged at the tail of the paste (such as the positive electrode active material layer) on the surface of the positive electrode collector in the positive electrode sheet, wherein a portion of the positive electrode sheet termination tape covers the paste on the surface of the positive electrode collector, and a portion of the positive electrode sheet termination tape covers the surface of the positive electrode collector (i.e., the empty foil on the surface of the positive electrode collector), as shown in the specific example. Figure 1 to Figure 3 shown.
[0048] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0049] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0050] Comparative Examples 1-6 and Examples 1-6
[0051] The lithium-ion batteries of Comparative Examples 1-6 and Examples 1-6 were all prepared according to the following preparation method, with the only difference being the positive electrode termination tape at the tail of the positive electrode paste and the non-aqueous electrolyte. The specific differences are shown in Table 1.
[0052] (1) Preparation of positive electrode
[0053] The positive electrode active material LiCoO 2, a binder polyvinylidene fluoride (PVDF), and a conductive agent acetylene black are mixed in a weight ratio of 97.2:1.3:1.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 9 to 12 μm; the coated aluminum foil is baked in an oven with 5 different temperature gradients, and then dried in an oven at 120°C for 8 hours, and then rolled and cut to obtain the required positive electrode sheets of different sizes. The specific electrode sheet widths are shown in Table 1.
[0054] (2) Negative electrode preparation
[0055] 96.5% by mass of artificial graphite negative electrode material, 0.1% by mass of single-walled carbon nanotube (SWCNT) conductive agent, 1% by mass of conductive carbon black (SP) conductive agent, 1% by mass of sodium carboxymethyl cellulose (CMC) binder and 1.4% by mass of styrene-butadiene rubber (SBR) binder were made into slurry by a wet process, coated on the surface of the negative electrode current collector copper foil, and dried (temperature: 85°C, time: 5h), rolled and die-cut to obtain negative electrode sheets of different sizes.
[0056] (3) Preparation of non-aqueous electrolyte
[0057] In a glove box filled with argon (water <10ppm, oxygen <1ppm), ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (PP), and 1,1,2,3-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether were mixed in a mass ratio of 1:1:3:2, and lithium salt (the specific amount and selection of lithium salt are shown in Table 1) was slowly added to the mixed solution, and stirred to obtain a non-aqueous electrolyte.
[0058] (4) Preparation of diaphragm
[0059] A polyethylene diaphragm with a thickness of 7 to 9 μm is selected.
[0060] (5) Preparation of positive electrode termination tape
[0061] 40 parts by weight of isooctyl acrylate, 3 parts by weight of butyl acrylate, 3 parts by weight of vinyl acetate, 3 parts by weight of acrylic acid, 5 parts by weight of isoprene rubber, 1 part by weight of pentaerythritol trimethacrylate, 1 part by weight of azobisisobutyronitrile, and 40 parts by weight of ethyl ester are stirred evenly at 80°C to obtain a mixed solution, and then a certain weight of cross-linking agent vinylene carbonate is added to the mixed solution, stirred evenly at room temperature, and coated on the surface of the PET substrate after mixing evenly to prepare a positive electrode termination tape. Among them, the positive electrode termination tape includes a PET substrate and a (meth) acrylic acid termination adhesive layer coated on the surface of the PET substrate, the specific amount of vinylene carbonate in the (meth) acrylic acid termination adhesive layer is shown in Table 1, and the area of the positive electrode termination tape is shown in Table 1.
[0062] (6) Preparation of lithium-ion batteries
[0063] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, and a positive electrode termination tape is attached to the end of the positive electrode sheet (the area of the positive electrode termination tape on both sides of the positive current collector is the same) to obtain a bare battery cell without liquid injection; the bare battery cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, formation, shaping, sorting and other processes, the required lithium-ion battery is obtained.
[0064] Table 1 Lithium ion batteries prepared in Comparative Examples 1-6 and Examples 1-6
[0065]
[0066] The electrochemical performance of the batteries obtained in the above comparative examples and embodiments was tested, and the relevant descriptions are as follows:
[0067] 45℃ cycle experiment: The batteries obtained in the above embodiments and comparative examples were placed in a (45±2)℃ environment and left to stand for 2-3 hours. When the battery body reached (45±2)℃, the battery was charged at a 1C constant current with a cut-off current of 0.05C. After the battery was fully charged, it was left for 5 minutes and then discharged at a 0.7C constant current to a cut-off voltage of 3.0V. The highest discharge capacity of the first three cycles was recorded as the initial capacity Q. When the cycle reached 400 times, the last discharge capacity of the battery was recorded as Q. 1 , and disassemble the 400T cycle battery to record whether lithium is deposited on the edge of the battery. The results are shown in Table 2.
[0068] The calculation formula used is as follows: Capacity retention rate (%) = Q 1 / Q×100%.
[0069] 85℃ high temperature storage for 8 hours: The batteries obtained in the above examples and comparative examples were placed at room temperature and subjected to three charge and discharge cycle tests at a charge and discharge rate of 0.5C, and then charged to a full charge state at a rate of 0.5C, and the highest discharge capacity Q of the first three 0.5C cycles was recorded respectively. 2 and battery thickness T 1 Store the fully charged battery at 85°C for 8 hours and record the battery thickness T after 8 hours. 2 and 0.5C discharge capacity Q 3 , the experimental data such as thickness change rate and capacity retention rate of the battery during high temperature storage were calculated, and the results are recorded in Table 2.
[0070] The calculation formula used is as follows:
[0071] Capacity retention rate (%) = Q 3 / Q 2 ×100%;Thickness change rate (%)=(T 2 -T 1 ) / T 1 ×100%
[0072] 130℃ thermal shock test: The batteries obtained in the above examples and comparative examples were heated by convection or circulating hot air oven at a starting temperature of 25±3℃, a temperature gradient of 5±2℃ / min, and the temperature was raised to 130±2℃. The test was terminated after maintaining for 60min, and the battery status results were recorded as shown in Table 2.
[0073] Table 2 Test results of batteries obtained from comparative examples 1-5 and examples 1-7
[0074]
[0075] It can be seen from the results in Table 2 that: It can be seen from the comparative examples and embodiments that the battery prepared by using lithium salt in the electrolyte in combination with the positive electrode termination tape can effectively improve the high temperature performance of the battery while solving the problem of lithium deposition at the edge of the electrode after battery cycling.
[0076] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A battery, comprising a positive electrode sheet, a negative electrode sheet, a non-aqueous electrolyte and a separator; a positive electrode sheet termination tape is provided at the paste tail of the positive electrode sheet; the non-aqueous electrolyte comprises a non-aqueous organic solvent and a lithium salt; The area of the positive electrode termination tape is A cm 2 , the concentration of the lithium salt is B mol / L, the width of the positive electrode sheet is C cm, in, The ratio of A to B is between 2 and 20; the ratio of A to C is between 1 and 3; The positive electrode termination tape comprises a PET substrate and a (meth) acrylic acid termination adhesive layer coated on the surface of the PET substrate; Wherein, a part of the positive electrode sheet termination tape covers the paste on the surface of the positive electrode current collector, and a part of the tape covers the surface of the positive electrode current collector; The area A of the positive electrode sheet termination tape refers to the area of the positive electrode sheet termination tape disposed on the surface of one side of the positive electrode current collector in the positive electrode sheet. The area A of the positive electrode sheet termination tape is within 3 cm 2 ~120cm 2 between ranges; The width C of the positive electrode sheet is in the range of 1 cm to 120 cm.
2. The battery according to claim 1, in, The concentration B of the lithium salt is 1 mol / L to 6 mol / L; Preferably, the concentration B of the lithium salt is 1.5 mol / L to 3 mol / L.
3. The battery according to any one of claims 1 to 2, in, The (meth)acrylic acid termination glue layer includes cross-linked modified (meth)acrylic acid and / or cross-linked modified (meth)acrylic acid ester, and the cross-linking agent of the cross-linked modified (meth)acrylic acid and / or cross-linked modified (meth)acrylic acid ester includes vinylene carbonate.
4. The battery according to claim 3, in, The content of the vinylene carbonate is 0.5 to 5 wt.% of the mass of the cross-linked modified (meth)acrylic acid and / or the cross-linked modified (meth)acrylic acid ester.
5. The battery according to any one of claims 1 to 4, in, The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer coated on one side or both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder.
6. The battery according to claim 5, in, The positive electrode active material is selected from lithium cobalt oxide or lithium cobalt oxide doped and coated with two or more elements of Al, Mg, Mn, Cr, Ti and Zr.
7. The battery according to claim 5 or 6, in, The chemical formula of the positive electrode active material is shown below: Li x Co 1-y1-y2-y3-y4 A y1 B y2 C y3 D y4 O 2 ; Among them, 0.95≤x≤1.05, 0.01≤y1≤0.1, 0.01≤y2≤0.1, 0≤y3≤0.1, 0≤y4≤0.1, and A, B, C, and D are selected from two or more elements of Al, Mg, Mn, Cr, Ti, and Zr.
8. The battery according to any one of claims 1 to 7, in, The electrolyte additive also includes at least one of 1,3-propane sultone, 1,3-propylene sultone, fluoroethylene carbonate, vinyl sulfite, vinyl sulfate, lithium dioxalatoborate, lithium difluorophosphate, lithium difluorooxalatophosphate and vinyl carbonate, and the content thereof accounts for 0 to 10 wt % of the total mass of the non-aqueous electrolyte.
9. The battery according to any one of claims 1 to 8, in, The non-aqueous organic solvent is selected from at least one of carbonates, carboxylates and fluoroethers, wherein the carbonate is selected from one or more combinations of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and methyl propyl carbonate; the carboxylates are selected from one or more combinations of ethyl propionate and propyl propionate; and the fluoroether is selected from 1,1,2,3-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
10. The battery according to any one of claims 1 to 9, in, The charging cut-off voltage of the battery is 4.45V or above.
11. The battery according to any one of claims 1 to 10, in, The battery is a lithium ion secondary battery.
Citation Information
Patent Citations
Cylindrical primary lithium battery and preparation method thereof
CN105977507A
Quick-charging and safe low-temperature lithium ion battery and manufacturing method thereof
CN111370752A
Wide-temperature-range high-performance primary lithium-manganese battery and preparation method thereof
CN112186210A
Nonaqueous electrolytic solution and lithium secondary battery
WO2004077599A1
